Targeted therapy of gastrointestinal stromal tumours - Jakhetiya, Ashish (World J Gastrointest Surg, 2016)
Gastrointestinal stromal tumours (GISTs) are mesenchymal neoplasms originating in the gastrointestinal tract, usually in the stomach or the small intestine, and rarely elsewhere in the abdomen. The malignant potential of GISTs is variable ranging from small lesions with a benign behaviour to fatal sarcomas. The majority of the tumours stain positively for the CD-117 (KIT) and discovered on GIST-1 (DOG-1 or anoctamin 1) expression, and they are characterized by the presence of a driver kinase-activating mutation in either KIT or platelet-derived growth factor receptor α. Although surgery is the primary modality of treatment, almost half of the patients have disease recurrence following surgery, which highlights the need for an effective adjuvant therapy. Traditionally, GISTs are considered chemotherapy and radiotherapy resistant. With the advent of targeted therapy (tyrosine kinase inhibitors), there has been a paradigm shift in the management of GISTs in the last decade. We present a comprehensive review of targeted therapy in the management of GISTs.